ANALYSIS OF THE COMPETITIVE ADVANTANGE MODEL OF MSMEs IN INDONESIA: URGENCY ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION, AND CUSTOMER CAPITAL AS PREDICTORS - Setyawati, Amelia; Setyawati, Christina Yanita; Kusuma, Rr. Chusnu Syarifa Diah; Nani, Nani (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
MSMEs are the backbone of the Indonesian economy, contributing a large part of the country's gross domestic product (GDP) and creating jobs for millions of people. In the face of increasingly fierce global competition, it is essential to understand the factors that influence the competitive advantage of MSMEs. The main objective of the research is to analyze the influence of entrepreneurial orientation, market orientation, and customer capital on competitive advantage. The sample in this research consisted of 160 respondents from MSME actors in the culinary sector in Indonesia who were determined using a convenience sampling approach. Data collection uses a questionnaire instrument, which is then distributed online. Data analysis uses the SPSS application by displaying data processing results through testing research instruments with validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis, entrepreneurial orientation, market orientation, and customer capital have a positive and significant effect on competitive advantage. Overall, this research contributes significantly to the theoretical understanding of MSME competitive advantage and provides practical guidance for the development, management and coaching of MSMEs in Indonesia. By strengthening entrepreneurial orientation, market orientation, and customer capital as predictors of competitive advantage, MSMEs can improve their market position and contribute more to economic growth and community development.